Respuesta :

Answer:

C

Step-by-step explanation:

using

x × y = [tex]\sqrt{x^2+y^2}[/tex] , then

2 × 4[tex]\sqrt{2}[/tex]

= [tex]\sqrt{2^2+(4\sqrt{2})^2 }[/tex]

= [tex]\sqrt{4+32}[/tex]

= [tex]\sqrt{36}[/tex]

= 6

[tex]\textsf {Applying this formula :}[/tex]

[tex]\mathsf {(x) \times (y) =\sqrt{x^{2} + y^{2}}}[/tex]

[tex]\textsf {Now take :}[/tex]

[tex]\mathsf {x = 2}\\\mathsf {y = 4\sqrt{2}}[/tex]

[tex]\mathsf {Solving :}[/tex]

[tex]\implies \mathsf {\sqrt{(2)^{2} + (4\sqrt{2})^{2}}}[/tex]

[tex]\implies \mathsf {\sqrt{4 + 32}}[/tex]

[tex]\implies \mathsf {6}[/tex]

ACCESS MORE